Aquaporin 4 distribution in the brain and its relevance for the radiological appearance of neuromyelitis optica spectrum disease - Ameli, Roxana; Guttmann, Charles R.G.; Prieto, Juan Carlos; Rollot, Fabien; Palotai, Miklos; Vukusic, Sandra; Marignier, Romain; Cotton, François; Anxionnat, René; Armspach, Jean-Paul; Audoin, Bertrand; Barillot, Christian; et al. (Journal of neuroradiology, 2021)
[Display omitted] To determine the precise incidence of lesions at sites of high Aquaporin-4 expression (hAQP4) and their possible association with known neuromyelitis optica spectrum disease (NMOSD) lesions patterns. A retrospective analysis of brain and, when available, spinal cord MRI scans of 54 NMOSD patients recruited among the French NMOSD cohort was performed. Brain lesions were annotated as MS-like, non-specific, or evocative of NMOSD. The topography of hAQP4 was reassessed by human brain atlas. The incidence of lesions in hAQP4 and their association with lesions evocative of NMOSD was estimated. Among those included (41/54 female, mean age: 45 years) 47/54 (87%) presented brain lesions. Twenty-six/47 (55%) had lesions in hAQP4. Thirty-two/54 patients (60%) had lesions considered evocative of NMOSD. The majority of them also presented lesions in hAQP4 (65%, 21/32). Patients with lesions in hAQP4 and lesions evocative of NMOSD demonstrated more extensive myelitis compared to the other patients (7 [6–10] versus 4 [3–5] vertebral segments, P=0.009). The coexistence of lesions evocative of NMOSD and in hAQP4 is associated with significantly more extensive myelitis, and might have pathophysiological and clinical significance.